SEKTOR UNGGULAN PROVINSI MALUKU PENDEKATAN TABEL INPUT-OUTPUT - , Siamin Loilatu ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The aims of this study are to identify leading sectors in the Province of Maluku